Autologous Transplantation As Consolidation for High Risk Aggressive T-Cell Non-Hodgkin's Lymphoma: A SWOG S9704 Intergroup Trial Subgroup Analysis - Stiff, Patrick J.; Li, Hongli; Cook, James R.; Constine, Louis S.; Couban, Stephen; Stewart, Douglas A.; Shea, Thomas C.; Porcu, Pierluigi; Winter, Jane N.; Kahl, Brad S; Smith, Sonali M.; Marcellus, Deborah; et al. (Blood, 2016)
Background: We recently clarified the use of consolidative autologous stem cell transplantation (ASCT) as first remission consolidation therapy for high grade diffuse aggressive T and B non-Hodgkin's lymphoma (NHL)in patients with high-intermediate (HI) or High (H) age adjusted IPI disease (Stiff et al, NEJM 369:1681). After receiving CHOP or R-CHOP for 5 cycles responding patients were randomized to either 3 more induction cycles or 1 cycle followed by an ASCT using either a BCNU or TBI based preparative regimen. We found a PFS but not OS advantage for those randomized to transplant and no differential treatment effect for those with T-NHL patients as compared to B-NHL in the initial analysis of this study. In light of Phase II data suggesting a value of early ASCT for T-NHL, a lack of randomized ASCT trials for T-NHL and the inferior prognosis for T-NHL as compared to B cell disease, we further evaluated this sub group, since a post hoc analysis of the entire trial did find a survival advantage for those with H IPI disease. This then provided a unique opportunity to evaluate the role of ASCT consolidation for T-cell NHL in the setting of a prospective randomized trial. Method: Among the 370 eligible B-NHL and T-NHL patients with HI/H IPI disease treated on this trial, 40 had a T-NHL phenotype and were the subject of this analysis. Individual patient files were re-reviewed and those randomized after the first 5 cycles of CHOP were further analyzed for stage, IPI group, histology (centrally reviewed), and response to induction and consolidation and updated survival outcome. Results: Of the 40 T-NHL patients enrolled on study, 28 (70%) were randomized after induction therapy, a similar ratio to the entire trial (68%). Twelve were not randomized; 1 was ineligible for study, and of the eligible 11, 9 were HI IPI and 8 had peripheral T cell (PTCL-NOS). These 11 were not randomized due to patient choice in 2, and all of the remaining 9 pts progressed early: 2 after C1; 3 after C3, 1 after C4, and 3 after C5. For the 28 randomized, their median age was 50 and 19 were males. Of the group, 21/28 had B symptoms at diagnosis, 14 had stage IV disease, and 18 and 10 were in the HI and H IPI groups respectively. Histologies included 11 with PTCL-NOS, 7 angioimmunoblastic and 10 anaplastic large cell NHL. At randomization 13 were to continue CHOP and 15, ASCT. Of the 15 assigned to ASCT, 3 did not undergo transplant (2-refusals, 1- unable to mobilize); 7 received the BCNU-etoposide-cyclophosphamide and 5 the TBI-etoposide-cyclophosphamide preparative regimen. The 5 year estimates of PFS and OS for the randomized ASCT vs CHOP only groups (intent to treat) were 40% vs 38% (p=0.56) and 40% vs 45% (p=0.98) respectively. We found no difference in outcome based on IPI group, histology or stage of disease. Interestingly, only 1/7 patients who received BCV as the ASCT preparative regimen are long term survivors vs 4/5 receiving the TBI-based regimen. Conclusions: We did not observe a PFS/OS advantage for those with high-risk T-NHL in first remission randomized to ASCT following CHOP induction vs CHOP alone in this retrospective analysis. In addition, the 30% early drop out rate before randomization due primarily to early progression strongly suggests that more optimal induction regimens need to be developed for this disease. While the numbers are small the finding that TBI based preparative regimens might be associated with a higher PFS is of interest and deserves further study. Support: NIH/NCI grants CA180888 and CA180819; Bristol-Myers Squibb. Contributions of Dr. Raymond R Tubbs, deceased, are gratefully acknowledged. [Display omitted] Porcu:miRagen: Other: Investigator in a clinical trial; celgene: Other: Investigator in a clinical trial; Millenium: Other: investigator in a clinical trial; Innate Pharma: Other: Investigator in a clinical trial. Winter:Pharmacyclics: Research Funding; Medivation: Other: Provision of investigational agent for clinical trial; Seattle Genetics: Research Funding; GSK: Research Funding. Kahl:This study was coordinated by the ECOG-ACRIN Cancer Research Group (Robert L. Comis, MD and Mitchell D. Schnall, MD, PhD, Group Co-Chairs) and supported by the National Cancer Institute of the National Institutes of Health under the following award number: Research Funding. Smith:Juno: Consultancy; TGTX: Consultancy; AbbVie: Consultancy; Celgene: Consultancy; Genentech: Consultancy, Other: on a DSMB for two trials ; Gilead: Consultancy; Portola: Consultancy; Amgen: Other: Educational lecture to sales force; Pharmacyclics: Consultancy. Rimsza:NCI/NIH: Patents & Royalties: L.M. Rimsza is a co-inventor on a provisional patent, owned by the NCI of the NIH, using Nanostring technology for determining cell of origin in DLBCL.. Fisher:Gilead: Consultancy; Seattle Genetics: Consultancy; Johnson and Johnson: Consultancy. Friedberg:Bayer: Honoraria, Other: Data Safety Monitoring Board.